THU0012 TGFβ receptor polymorphisms in systemic sclerosis related pulmonary arterial hypertension: Results from a multicenter eustar study of european caucasian patients. (23rd January 2014) - Koumakis, E.; Wipff, J.; Matucci-Cerinic, M.; Riemekasten, G.; Airo, P.; Cusi, D.; Wichmann, H.E.; Müller-Ladner, U.; Vlachoyiannopoulos, P.; Chiocchia, G.; Allanore, Y.
Abstract : Background: Pulmonary arterial hypertension (PAH) is currently an important challenge in SSc and given the severity of this condition and the poor understanding of its risk factors and pathogenesis, there is an urgent need to identify novel risk factors and biomarkers for the development of SSc related PAH (SSc-PAH). Mutations of TGFβ-receptor genes strongly contribute to idiopathic and familial PAH. Therefore, TGFβ-receptor family genes represent good candidates for the study of genetic susceptibility to SSc-PAH. Objectives: To explore the genetic bases of SSc-PAH, we combined direct sequencing and genotyping of candidate genes encoding TGFβ-receptor family members. Methods: TGFβ-receptor genes BMPR2, ALK1, TGFR2 and ENG, were sequenced in 10 SSc-PAH patients, 9 SSc, and 7 controls to identify potentially deleterious variations. In addition, 22 single-nucleotide polymorphisms (SNPs) of these 4 candidate genes were tested for association in a first set of 824 French Caucasian SSc patients (including 54 SSc-PAH) and 939 controls. The replication set consisted of 1516 European SSc (including 219 SSc-PAH) and 3129 controls from the EUSTAR network. Results: No mutation was identified by direct sequencing. However, interestingly, two repertoried SNPs, ENG rs35400405 and ALK1 rs2277382, were found in SSc-PAH patients only. Rs35400405, located at codon 14 of exon 1 in the ENG gene, introduces an in-frame ATG sequence downstream of the usual initiating codon that might result in the loss of the first amino acids. Rs2277382 is located in the promoter of the ALK1 gene. The genotyping of 22 SNPs including the 2 latter revealed no association with SSc. Nethertheless, genetic association was observed between the SSc-PAH subphenotype and ALK1 rs2277382 (Padj=0.0066; OR=2.13, 95%CI [1.24-3.65]). Following the results obtained in the discovery set, we selected the ALK1 rs2277382 SNP to be solely investigated in the EUSTAR replication populations (French, Northern European, Italian and Eastern European). Genotype frequencies of the rs2277382 variant were in Hardy-Weinberg equilibrium in the control populations of these replication sets. No association was observed between the ALK1 rs2277382 T allele and either SSc or the SSc-PAH subphenotype. Meta-analysis of the combined discovery and replication sets including a total of 2340 SSc patients, 273 SSc-PAH and 4068 controls did not provide evidence for an association between ALK1 rs2277382 and SSc-PAH (p=0.123, OR=0.79, 95%CI [0.59-1.07]). Conclusions: This study demonstrates the lack of association between these TGFβ-receptor gene variants and SSc-PAH using a synergistic strategy combining sequencing and genotyping methods. Disclosure of Interest: E. Koumakis: None Declared, J. Wipff: None Declared, M. Matucci-Cerinic: None Declared, G. Riemekasten: None Declared, P. Airo: None Declared, D. Cusi: None Declared, H. E. Wichmann: None Declared, U. Müller-Ladner: None Declared, P. Vlachoyiannopoulos: None Declared, G. Chiocchia: None Declared, Y. Allanore Grant/Research support from: Pfizer Ltd.